Pengaruh Intellectual Capital Terhadap Kinerja Keuangan Bank Syariah di Indonesia - Yuni Shara (Forum Kerjasama Pendidikan Tinggi, 2024)
This study aims to analyse the effect of Intellectual Capital on the financial performance of Islamic banks in Indonesia. This study uses a quantitative approach with the Value Added Intellectual Coefficient (VAIC™) model to measure three main elements: Human Capital Efficiency (HCE), Structural Capital Efficiency (SCE), and Capital Employed Efficiency (CEE). This study was conducted by collecting data from the financial statements of Islamic banks in Indonesia during the 2019-2022 period, involving 12 Islamic banks registered with the Financial Services Authority (OJK) as samples. The analysis method used is regression analysis with the Partial Least Squares (PLS) approach to test the relationship between Intellectual Capital and Return on Assets (ROA) as an indicator of financial performance. The analysis shows that Intellectual Capital has a positive and significant effect on financial performance. Human Capital Efficiency has the greatest influence on financial performance, followed by Capital Employed Efficiency and Structural Capital Efficiency. The findings confirm that investment in human capital and efficient management of organisational structures play an important role in improving financial performance. This study provides an important contribution in understanding the role of Intellectual Capital in the Islamic banking sector, as well as practical implications for bank management to improve efficiency and financial performance through intellectual capital development. The results of this study can provide recommendations for Islamic bank management regarding the importance of effective intellectual capital management to achieve optimal financial performance.